STRATEGI GURU DALAM MENYUSUN MODUL AJAR KURIKULUM MERDEKA PADA MATA PELAJARAN BAHASA INDONESIA DI SD NEGERI BALE ATU BENER MERIAH: penelitian deskriptif - Nahdalia; Husaini; Misrina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACTThis research is motivated by the implementation of the Merdeka Curriculum, which provides teachers with the flexibility to design contextual and student-centered learning processes. The study aims to describe the strategies employed by teachers in developing teaching modules for the Merdeka Curriculum in the subject of Bahasa Indonesia at SD Negeri Bale Atu, Bener Meriah Regency. However, in practice, teachers still face various challenges in independently preparing teaching modules. This study uses a qualitative approach with a case study method. The research subjects were five Bahasa Indonesia teachers for grades III, IV, and V at SD Negeri Bale Atu. Data collection techniques included in-depth interviews, questionnaires, and documentation. The collected data were analyzed descriptively through data reduction, data presentation, and drawing conclusions.The findings show that the strategies used by teachers in preparing teaching modules include: understanding learning objectives and outcomes, aligning materials with student characteristics, utilizing digital resources, compiling modules gradually, and collaborating through teacher working group (KKG) forums. Challenges encountered include limited understanding of the structure of teaching modules, lack of technical training, time constraints, and limited access to learning resources. Nevertheless, teachers employed various innovations to overcome these obstacles, such as self-directed learning, participating in online training, and developing contextual and adaptive modules to meet students’ needs.This research recommends the importance of practical training and intensive mentoring for teachers in preparing teaching modules for the Merdeka Curriculum, as well as the need to improve facilities and access to learning resources in schools.